Ultrasound imaging in paediatric rheumatology. Issue 6 (December 2020) - Windschall, Daniel; Malattia, Clara
Abstract: The role of ultrasound imaging in the diagnosis and monitoring of paediatric rheumatic diseases with special emphasis on recent scientific work regarding the evidence base and standardization of this technique is being reviewed. An overview of the most important practical aspects for the use of musculoskeletal ultrasound in a clinical setting is also provided. Huge scientific efforts and advances in recent years illustrate the increasing importance of musculoskeletal ultrasound in pediatric rheumatology. Several studies focused on setting an evidence-based standard for the ultrasound appearance of healthy and normal joints in children of all age groups. Physiologic vascularization and ossification were two main aspects of these studies. Other publications demonstrate that ultrasound imaging is also an important and useful tool to detect pathology as synovitis, tenosynovitis or enthesitis in children and to monitor pediatric patients with rheumatic conditions. Important practical aspects include training in the use of correct ultrasound techniques, as well as knowledge and experience of normal pediatric sonoanatomy and the appearance of pathological findings on ultrasound.